Inhibition of trehalase activity enhances trehalose accumulation in transgenic plants. - Goddijn, O J (1997)
As a first step toward the exploitation of the disaccharide trehalose as a stress-protective and preservative agent in plants, we engineered trehalose biosynthesis in tobacco (Nicotiana tabacum) and potato (Solanum tuberosum) by introducing the otsA and otsB genes from Escherichia coli, which encode trehalose-6-phosphate synthase and trehalose-6-phosphate phosphatase, respectively. In leaves of transgenic tobacco plants, very low levels of trehalose accumulation were obtained (0.11 mg g-1 fresh weight), whereas in transgenic potato tubers, no trehalose accumulated at all. Plant trehalase activity was shown to affect the accumulation of trehalose in these plants. An increase in trehalose accumulation, up to 0.41 and 4.04 mg g-1 fresh weight in tobacco leaves and potato micro-tubers, respectively, was noted when the potent trehalase inhibitor validamycin A was added to in vitro plants and to hydroponically grown greenhouse plants. Stunted growth and the formation of lancet-shaped leaves by trehalose-accumulating tobacco plants suggest a negative effect of trehalose biosynthesis on N. tabacum development. It is surprising that experiments with wild-type plants cultured in the presence of validamycin A indicate that, despite current belief, the capacity to synthesize trehalose may not be restricted to primitive phyla of vascular plants and certain "resurrection plants," but may exist throughout the angiosperms.